PENGARUH MEDIA PAKGATA BERBASIS AUGMENTED REALITY DENGAN PENDEKATAN TARL DAN CRT TERHADAP PEMAHAMAN SISWA KELAS IV SD TENTANG JEJAK KARBON - Anita Kuniawati; Rosmiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This classroom action research aims to examine the effectiveness of the Augmented Reality (AR)-based learning media PAKGATA (Paku Gantung Bercerita), integrated with the Teaching at the Right Level (TaRL) and Culturally Responsive Teaching (CRT) approaches, in enhancing fourth-grade elementary students’ understanding of the carbon footprint concept. The research was conducted in two cycles involving 28 students from class 4D at SDN Kaliasin 1 Surabaya. In the first cycle, the media did not yet include AR features and the worksheets were not differentiated, resulting in low student engagement and a passive learning environment. In the second cycle, the AR-based PAKGATA media was enhanced and integrated with TaRL and CRT through leveled and contextual worksheets. The results showed a significant improvement in students’ learning outcomes, with the average score increasing from 61.29 in Cycle I to 88.00 in Cycle II. The calculated effect size using Cohen’s d was 2.30, indicating a very large effect. Observational and interview data further supported the quantitative findings, revealing increased student participation, engagement, and contextual understanding. This study concludes that the integration of AR-based PAKGATA media with TaRL and CRT approaches is highly effective in improving elementary students’ environmental literacy, particularly in understanding the carbon footprint concept.